FROM JASPERS TO NIETZSCHE: PHILOSOPHY OF EXISTENCE IN VISUAL REPRESENTATION - Petra Cepková; Barbora Kováčová (Interdisciplinary Science Studies, 2025)
The study explores the connections between the philosophy of existence and documentary photography. It draws on the concepts of prominent thinkers such as Karl Jaspers, Martin Heidegger, Gilles Deleuze, Friedrich Nietzsche, Emmanuel Levinas, Roland Barthes and Susan Sontag. It analyses how their ideas translate into the visual medium. Documentary photography is understood here not only as an aesthetic record, but above all as a space of confrontation with borderline situations, an ethical appeal, and a visual testimony to human dignity and vulnerability. In the text, the authors address the issues of altruism and egoism in social relations and their visualisation through the photographic image, which oscillates between an aesthetic reception and a call for engagement. The final section presents the possibility of linking documentary photography with action art as a strategy of social participation and reflection.